USING DIGITAL STORYBOOK IN A JAPANESE ONLINE CLASS TO SUPPORT A1-LEVEL WRITING SKILLS - Devina, Nadia Irma Della; Hamamah, Hamamah; Rohmah, Zuliati; Muttaqin, Syariful (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Nowadays, although face-to-face learning is conducted in various educational institutions, there is still a great demand for online learning, especially in non-formal educational institutions. Online learning helps students to study without being constrained by distance and have more flexible time. This study wants to explore the application of digital storybooks as an alternative learning media in an online language program to develop student’s writing skills in Japanese and report on the results after the program. This study employed a case study design where the data is presented descriptively to report the implementation of a multimodal text in the form of a digital storybook and the responses of 4 Japanese language learners as both the participants of this study and an online language course. Naturalistic observation became the primary instrument where all activities were recorded, with the addition of writing practice to gain an understanding of students’ comprehension of the given lesson as the second instrument. The results of using multimodal texts in the classroom showed a positive impact. This is shown in the students' writing after participating in learning with multimodal texts. The improvement in the students' writing skills was shown on the students' worksheets in which some students added place settings, time information, and also the correct particles. In short, the usage of the digital storybook enhances students' writing skills and develops their creativity through an enjoyable way of learning.